Design spray rail and configuration and its effect on resistance of planning craft - 458847 Sharizad Abd. Talib (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Marine Technology)) - Universiti Teknologi Malaysia, 2003